The Parable of the Samaritan: A Countercultural Proposal - Polo Medina, Paola (2020)
This article tries to approach an interpretative reading of the Parable of the Samaritan from the text and the context to deepen it; that is to say, to go beyond a simple reading whose teaching is Christian practice but seen in isolation. It aims to introduce the reader to the text from a Christological perspective. That is, to see in the parable a metaphor of Jesus of Nazareth and his action in favor of the Kingdom of justice that appeals to the God whose entrails are of mercy. And, in this sense - as E. Schweizer says - see how Jesus is the parable of God. Therefore, the parable contains much more than a simple teaching. It expresses the infinite and saving love of God, made in the person of Jesus of Nazareth.